Matrimonial offences under the Algerian law : an apparaisal - Smail, Akakba (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2015)
This study examines the current legal provisions in protecting the matrimonial relationship and restraining the illegal acts and extramarital relationships from each or both spouses in the Algerian Law. The study starts from the regulations of the matrimonial relationship under Islamic Law as it is the main source of the Algerian Family Code. Meanwhile, the study defines and classifies the matrimonial offences in the light of Islamic Law. Furthermore, the study highlights analytically the provisions of the marriage contract and its dissolution within the Algerian Family Code that provides the right for the wife to ask for divorce (tatlīq) from the judge in accordance with Article 51. In this respect, many harmful deeds as grounds to ask for divorce (tatlīq) can be considered as matrimonial offences in spite of the absence of special provisions for this kind of offences within the Family Code. Actually, in the absence of a particular law whether for the matrimonial offences or the domestic violence, this study has taken by analysis the rules of the Algerian Penal Code to show to what extent the Algerian legislator legally protects the marital relationship. Based on that, the study shows that the present provisions in relation to the matrimonial offences in Algerian Law are inadequate to provide legal protection to the matrimonial relationship as the constituent element of the family which is the main entity of society. Besides, this study also identifies measures in terms of positive efforts in legal reform to improve the current situation.